MODERN MUSIC BANDS IN THE FESTIVAL MOVEMENT OF UKRAINE - Berezhnyk, Sviatoslav (Вісник КНУКіМ. Серія «Мистецтвознавство», 2016)
The article concerns the modern landscape of music festivals in Ukraine. The author examines the creative work of the new bands in the festival movement and traces their impact on the development of national musical culture.